2019
DOI: 10.1002/brb3.1420
|View full text |Cite|
|
Sign up to set email alerts
|

The psychoactive cathinone derivative pyrovalerone alters locomotor activity and decreases dopamine receptor expression in zebrafish (Danio rerio)

Abstract: IntroductionPyrovalerone (4‐methyl‐β‐keto‐prolintane) is a synthetic cathinone (beta‐keto‐amphetamine) derivative. Cathinones are a concern as drugs of abuse, as related street drugs such as methylenedioxypyrovalerone have garnered significant attention. The primary mechanism of action of cathinones is to inhibit reuptake transporters (dopamine and norepinephrine) in reward centers of the central nervous system.MethodsWe measured bioenergetic, behavioral, and molecular responses to pyrovalerone (nM‐µM) in zebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…In conclusion, it was confirmed that the effect on locomotory activity is common across different types of synthetic cathinones [ 23 , 30 , 33 , 36 , 41 , 42 , 57 , 59 , 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…In conclusion, it was confirmed that the effect on locomotory activity is common across different types of synthetic cathinones [ 23 , 30 , 33 , 36 , 41 , 42 , 57 , 59 , 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 62%
“…Pyrovalerone was directly administrated to zebrafish larvae using a special 96-well plate precoated with pyrovalerone. This study reported changes in locomotor activities, showing hyperactivity and higher movement after pyrovalerone administration [ 57 ]. This result was observed also in adult zebrafish after α-pyrrolidinopentiophenone exposure [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our results, no morphometric changes in embryonic development and cumulative mortality were observed in zebrafish exposed to venlafaxine, a chiral antidepressant, at s concentrations ranging from 0.3 to 3000 μg/L (Ribeiro et al 2022 ). Also, the exposure to pyrovalerone, a synthetic cathinone, did not cause mortality in embryos and larvae zebrafish (Souders et al 2019 ). In contrast, Kalichak et al ( 2016 ) showed that the exposure of zebrafish to fluoxetine, a classical serotonin reuptake inhibitor antidepressant, decreased the heart rate and length of larvae at the highest concentration (99 mg/L).…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity effects of NPS, including some SC, have also been reported on aquatic organisms. For instance, exposure to pyrovalerone (MPP; ranging from 113.00 to 11,310.00 µg L −1 ) caused changes in the swimming behavior of zebrafish larvae ( Danio rerio ) [ 17 ] and changes in oxidative status and reproductive parameters were observed in microcrustacean Daphnia magna exposed to methamphetamine at 0.05 and 0.50 µg L −1 [ 18 ], and growth inhibition was observed and in protozoan Tetrahymena thermophila exposed to ( S )-ketamine (>5000.00 µg L −1 ) [ 19 ]. Understanding the impact of NPS on ecosystems is crucial to provide essential data for establishing environmental safety levels, environmental policies, and mitigation actions.…”
Section: Introductionmentioning
confidence: 99%